Association between level of suicide risk, characteristics of suicide attempts, and mental disorders among suicide attempters - Subin Park; Yeeun Lee; Tak Youn; Byung Soo Kim; Jong Ik Park; Haesoo Kim; Hyo Chu Lee; Jin Pyo Hong (BMC, 2018)
Abstract Background Past attempted suicide is a strong predictor of future suicide risk, but the risk varies among suicide attempters. Hence, it is important to clarify distinguishing features of lifetime attempters with a high level of current suicide risk for efficient preventive management. Methods We compared characteristics of suicide attempts and clinical characteristics among high-, moderate-, and low-risk attempters. Among the total of 6022 participants in the Korean Epidemiologic Catchment Area study, 193 reported a suicide attempt in their lifetime, 36 of which had high, 126 moderate, and 30 low levels of current suicide risk (1 incomplete response). Results High-risk suicide attempters had more past attempts compared with moderate- and low-risk suicide attempters. Suicide attempts were closely linked to a wide range of psychiatric comorbidities regardless of degree of current level of suicide risk, but the relative risk for having at least one mental disorder was the highest in high-risk attempters. Specifically, the relative risks for depressive disorder, anxiety disorders including obsessive-compulsive disorder and post-traumatic stress disorder, and substance use disorders were higher in high-risk attempters, and relative risk for somatoform disorder was higher in low-risk attempters than others. Conclusions Our findings indicated that special attention is required for suicide attempters with a history of repeated attempts and current mental disorders, particularly anxiety disorders.